The unipotent Albanese map and Selmer varieties for curves - Kim, M (Research Institute for Mathematical Sciences, Kyoto University, 2009)
We study the unipotent Albanese map that associates the torsor of paths for p-adic fundamental groups to a point on a hyperbolic curve. It is shown that the map is very transcendental in nature, while standard conjectures about the structure of mixed motives provide control over the image of the map. As a consequence, conjectures of ‘Birch and Swinnerton-Dyer type’ are connected to finiteness theorems of Faltings-Siegel type.